2006
DOI: 10.1002/j.0022-0337.2006.70.10.tb04182.x
|View full text |Cite
|
Sign up to set email alerts
|

Injury Reports in a Dental School: A Two‐Year Overview

Abstract: As teaching institutions, it is vital for dental schools to collect data on accidental injuries to identify potential problems, improve the quality of care of patients, and educate future practitioners about risk management. Our data reveal important trends concerning such injuries. These data were compiled over a two-year period (2001-03) from accident reports at one dental school. We categorized the accidents as follows: source (instrument causing the injury), recipient of injury, time of day, location withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
31
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 18 publications
(21 reference statements)
13
31
0
3
Order By: Relevance
“…These injuries could have been avoided by the correct placement of the hand‐piece sideways and away from the operating field and using protective caps on scaler tips. Our study found that fingers were the most common anatomical sites of injury, which is in agreement with findings reported by other research.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These injuries could have been avoided by the correct placement of the hand‐piece sideways and away from the operating field and using protective caps on scaler tips. Our study found that fingers were the most common anatomical sites of injury, which is in agreement with findings reported by other research.…”
Section: Discussionsupporting
confidence: 92%
“…Higher PEIs in our study were due to dental anaesthetic needles, followed by bur and scaler tips, a breakdown consistent with other published reports from dental teaching institutes. A high percentage of percutaneous incidents occurred as a result of needle recapping which is also in agreement with the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[1][2][3] Existing dental anesthesia curriculums and educational programs have not emphasized techniques other than using the finger for retraction of mucosa. [4][5][6][7] Literature presents cases of needlestick injuries (NSIs) when finger is used to retract mucosa to deliver anesthesia. 8,9 Innovations towards dental anesthesia delivery have progressed throughout the years.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Innovations towards dental anesthesia delivery have progressed throughout the years. 1,4,[10][11][12][13] In addition, various instruments exist both in clinical practice and on the market to aid in retraction (cheek retractor, tongue depressor etc). 1,[14][15][16] In 2010, a device was approved for purchase in the United States for use during dental anesthesia delivery (Fig.…”
Section: Introductionmentioning
confidence: 99%